Design and Optimization of Fuel Cells: A Case Study on Polymer Electrolyte Membrane Fuel Cell Power Systems for Portable Applications - Orhan, Mehmet Fatih (2022)
Fuel cells are energy conversion devices that directly convert chemical energy of fuels such as hydrogen to useful work with negligible environmental impact and high efficiency. This study deals with thermodynamic analysis and modeling of polymer electrolyte membrane fuel cell (PEMFC) power systems for portable applications. In this regard, a case study of powering a computer with a PEMFC is presented. Also, an inclusive evaluation of various parameters such as voltage polarization, overall system efficiency, power output, and heat generation is reported. In addition, a parametric study is conducted to study the effect of many design and operation parameters on the overall efficiency. Results show the direct influence of current density and temperature values on optimization of the design parameters in PEMFCs.